Outcomes of Laparoscopic Cholecystectomy Compared to the Open Procedure in Patients with Gallbladder Disease: A Systematic Review - Elizabeth; Irene (International Medical Journal Corp. Ltd, 2024)
Background: Gallbladder disease progresses with gallbladder blockage, infection, or inflammation. The clinical manifestations of gallbladder disease include cholecystitis, gallstones, empyema/abscess, gangrene, sclerosing cholangitis, acalculous condition, and abnormal tissue growth. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using Medline, Science Direct, Scopus and Embase, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Early laparoscopic cholecystectomy compared with delayed intervention, early laparoscopic cholecystectomy should be preferred for treatment of gallbladder disease